The Inhibitory Effects of Slow-Releasing Hydrogen Sulfide Donors in the Mechanical Allodynia, Grip Strength Deficits, and Depressive-Like Behaviors Associated with Chronic Osteoarthritis Pain - Gerard Batallé; Laura Cabarga; Olga Pol (MDPI AG, 2019)
Osteoarthritis and its associated comorbidities are important clinical problems that have a negative impact on the quality of life, and its treatment remains unresolved. We investigated whether the systemic administration of slow-releasing hydrogen sulfide (H2S) donors, allyl isothiocyanate (A-ITC) and phenyl isothiocyanate (P-ITC), alleviates chronic osteoarthritis pain and the associated emotional disorders. In C57BL/6 female mice with osteoarthritis pain induced by the intra-articular injection of monosodium iodoacetate, we evaluated the effects of repeated administration of A-ITC and P-ITC on the (i) mechanical allodynia and grip strength deficits; (ii) emotional conducts; and (iii) glial activity and expression of inducible nitric oxide synthase (NOS2), phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt), and antioxidant enzymes (heme oxygenase 1, NAD(P)H:quinone oxidoreductase-1, glutathione S-transferase mu 1 and alpha 1) in the hippocampus. The administration of A-ITC and P-ITC inhibited the mechanical allodynia, the grip strength deficits, and the depressive-like behaviors accompanying osteoarthritis. Both treatments inhibited microglial activation, normalized the upregulation of NOS2 and PI3K/p-Akt, and maintained high levels of antioxidant/detoxificant enzymes in the hippocampus. Data suggest that treatment with low doses of slow-releasing H2S donors might be an interesting strategy for the treatment of nociception, functional disability, and emotional disorders associated with osteoarthritis pain.